(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
This research aims to investigate in the strength of sand soil treated with different percentages (3%, 5%, 7%) of cement and (5%, 10%, 7%, 15%) of lime, two different of the dry unit weights (14.4,15.8) kN/m3. The specimens were examining after (28) days. The study included a number of unconfined compression tests. The UCS increased as cement content increased. It is noticed that the axial stress increases 225% for soil with gd =15.8 kN/m3 and 153% for soil with gd =14.4 kN/m3 with increasing cement content from 3% to 7%.The results show that the UCS increased as lime content increased It is noticed that the axial stress increases 165% for soil with gd =15.8 kN/m3 and 238% for soil with gd =14.4 kN/m3 with increasing lime content from 5% to 15%, as the soil showed a significant improvement in the strength of cement-treated soil compared to the lime-treated soil.